Soft polyether urethane foam and urethane mask

The development of a soft polyether urethane foam with heat sealing properties and high elongation addresses the durability and bonding issues of polyester foam, providing a durable and reusable urethane mask solution.

JP7628170B2Active Publication Date: 2025-02-07INOAC CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023500973
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-30
Filing Date
2022-02-22
Publication Date
2025-02-07
Estimated Expiration
2042-02-22

AI Technical Summary

Technical Problem

Soft polyester urethane foam used in urethane masks is prone to hydrolysis, leading to poor durability and high production costs, while soft polyether urethane foam lacks heat sealing properties, making it unsuitable for applications requiring bonding.

Method used

A soft polyether urethane foam with enhanced heat sealing properties and high elongation, characterized by specific density and composition, including polyols, polyisocyanates, and catalysts, which allows for heat sealing and durability.

Benefits of technology

The foam achieves effective heat sealing, maintains durability through resistance to hydrolysis, and is suitable for urethane masks, ensuring repeated use without deterioration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628170000001
    Figure 0007628170000001
  • Figure 0007628170000002
    Figure 0007628170000002
  • Figure 0007628170000003
    Figure 0007628170000003
Patent Text Reader

Abstract

The purpose of the present invention is to provide flexible polyether urethane foam which is heat-sealable, is less apt to hydrolyze, is less apt to be deteriorated by laundering, etc., has high durability, and is suitable for urethane masks. The flexible polyether urethane foam is one formed from a composition of starting materials for polyurethane foam production. The flexible polyether urethane foam has an elongation (in accordance with JIS K6400-5) of 100% or higher and a density (in accordance with JIS K7222) of 10-150 kg / m3 and is heat-sealable.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flexible polyether urethane foam having heat sealability and a urethane mask. [Background technology]

[0002] A urethane mask made of soft urethane foam has been proposed as a mask for covering a part of the face including the mouth and nostrils.

[0003] Flexible urethane foams include flexible polyether urethane foams and flexible polyester urethane foams. Flexible polyether urethane foam has poor heat sealability and is difficult to hydrolyze. Flexible polyester foam has excellent heat sealability and is easily hydrolyzed. Heat sealing is a type of thermal fusion, in which layers of soft urethane foam are stacked and heated and compressed using a hot plate or the like to join (adhere) the layers of soft urethane foam together.

[0004] A conventional urethane mask has left and right halves each made of soft polyester urethane foam, and the left and right halves are joined together at the center by heat sealing (Patent Document 1). In addition, the soft polyester urethane foam used in urethane masks is treated to remove membranes (cell membranes) to ensure breathability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-3275 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, flexible polyester urethane foam is susceptible to hydrolysis and therefore is prone to deterioration due to washing, etc., and has the problem of being poor in durability. In addition, there is a problem that the cost of performing the film removal treatment on the flexible polyester urethane foam is high, and further, there is a problem that an odor remains in the flexible polyester urethane foam depending on the film removal treatment.

[0007] Although conventional flexible polyether urethane foams are resistant to hydrolysis, they have poor heat sealability and are therefore not suitable for applications requiring heat sealing.

[0008] The present invention has been made in consideration of the above-mentioned points, and aims to provide a soft polyether urethane foam that has heat sealability, is resistant to hydrolysis, is less susceptible to deterioration due to washing, etc., and is highly durable, and a urethane mask made from this soft polyether urethane foam. [Means for solving the problem]

[0009] The first method is to use a material with an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 The soft polyether urethane foam is characterized by having heat sealability.

[0010] The second means is a urethane mask comprising the soft polyether urethane foam of the first means.

[0011] In the first and second aspects, the flexible polyether urethane foam of the present invention may be a laminate in which at least one of a fiber layer, a flexible polyurethane foam, and a cloth layer is laminated. For example, a first modified embodiment includes a first substrate which is the soft polyether urethane foam of the present invention, a fiber layer (intermediate fiber layer) laminated on one side of the first substrate or the second substrate, and a second substrate which is a soft polyurethane foam laminated on the fiber layer (intermediate fiber layer) (first substrate / fiber layer / second substrate). In a second variation, the second substrate is a fabric layer. As a third modified embodiment, a fiber layer is laminated on one side of the flexible polyether urethane foam of the present invention. In relation to the first modified embodiment or the second modified embodiment, this third modified embodiment is the case where there is no second substrate. A fourth variation is where a flexible polyurethane foam or fabric layer is laminated to one side of the flexible polyether urethane foam of the invention. The fiber layer is preferably made of nanofibers.The flexible polyurethane foam is preferably a flexible polyurethane foam having an open cell structure. Heat sealing of a laminate in which at least one of a fiber layer, a flexible polyurethane foam, and a fabric layer is laminated on one side of the flexible polyether urethane foam of the present invention can be carried out, for example, with the intended joining portions of the flexible polyether urethane foam of the present invention overlapped. If the second substrate has heat sealability, the second substrate side may be overlapped and joined, or the first substrate and the second substrate may be joined. Effect of the Invention

[0012] The flexible polyether urethane foam of the present invention has heat-sealing properties and can be bonded by heat sealing like polyester urethane foam, making it suitable for applications requiring bonding. Furthermore, the polyether urethane foam of the present invention has an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 It is suitable as a component of a urethane mask, and is suitable for a urethane mask that requires heat sealing. Furthermore, the soft polyether urethane foam of the present invention is less susceptible to hydrolysis than polyester urethane foam, and therefore is less susceptible to deterioration due to washing and the like, and has high durability, so that it can be used in urethane masks and washed repeatedly. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a perspective view showing a mask according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a partially cutaway perspective view of a laminate according to a first modified embodiment of the present invention. [Diagram 3] 1 is the first table showing the formulations and physical properties of the comparative examples and the examples. [Figure 4] 2 is a second table showing the compositions and physical properties of each example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the flexible polyether urethane foam of the present invention will be described.

[0015] The flexible polyether urethane foam of the present invention has an elongation (based on JIS K6400-5) of 100% or more, preferably 200% or more, and more preferably 300% or more. There is no particular upper limit. In practical terms, it is preferably 700% or less. By having an elongation of 100% or more, for example, when used in a mask, it is easy to adhere to the face and the feeling of pressure can be reduced.

[0016] The flexible polyether urethane foam of the present invention has a density (in accordance with JIS K7222) of 10 to 150 kg / m 3 and preferably 20 to 130 kg / m 3 and more preferably 25 to 115 kg / m 3 and more preferably 30 to 100 kg / m 3 If the density is low, the strength of the flexible polyether urethane foam may decrease, whereas if the density is high, the stretchability of the flexible polyether urethane foam may decrease.

[0017] The flexible polyether urethane foam of the present invention has a heat sealability such that the result of the heat seal strength test shown below is 100 kPa or more, preferably 200 kPa or more, and more preferably 500 kPa or more. In the heat seal strength test, two test pieces measuring 100 mm in length, 30 mm in width, and 10 mm in thickness are overlapped, and a 20 mm area from one end is heat-sealed by sandwiching it between a 180°C hot plate and applying a pressure of 1.3 megapascals (MPa) for 30 seconds. The other ends of the two test pieces are then opened 180 degrees and pulled in opposite directions at a tensile speed of 500 mm / min. The strength at which the two test pieces peel off is recorded as the heat seal strength.

[0018] The soft polyether urethane foam of the present invention has a breathability (based on JIS L1096A method) of preferably 5 cm 3 / cm 2 / sec or more, and more preferably 10 cm 3 / cm 2 / sec or more, and more preferably 15 cm 3 / cm 2 The flexible polyether urethane foam of the present invention has good breathability, and therefore can reduce breathlessness when used as a mask.

[0019] The flexible polyether urethane foam of the present invention is formed by foaming a composition of raw materials for producing polyurethane foam, which comprises a polyol, a polyisocyanate, a catalyst and a blowing agent.

[0020] The foaming of the flexible polyether urethane foam of the present invention is preferably slab foaming. Slab foaming is a method in which a composition of raw materials for producing polyurethane foam is mixed and discharged onto a belt conveyer, and foamed at atmospheric pressure and room temperature. The foamed flexible polyether urethane foam is made into a sheet of a predetermined thickness by a skiving process. The sheet is then punched to a predetermined shape, and predetermined parts of the predetermined shape are further joined by heat sealing (melting adhesion) to form a desired article.

[0021] One embodiment of a mask made from the flexible polyether urethane foam of the present invention is shown in FIG. The punched-out body 10A shown in Fig. 1 (1-A) is formed by punching out the soft polyether urethane foam sheet of the present invention into a mask shape. Reference numeral 13 denotes openings for ear hanging. The punched piece 10A is folded over at a central portion 15, which is the left-right center of the face, and as shown in Fig. 1 (1-B), is heat-sealed at a predetermined width along the central portion 15 to form the mask 10. The shaded portion indicated by the reference symbol 16 is the heat-sealed portion. The heat-sealed area of ​​the heat-sealed portion 16 of the central portion 15 is determined so that when the mask 10 is spread out to the left and right for use, the central portion 15 expands outward to assume a three-dimensional shape that corresponds to the bulging of the nose. The mask formed from the soft polyether urethane foam of the present invention is not limited to the shape of the mask shown in FIG. Heat-sealed portions that are wider than necessary may be cut. They may be cut so as to have a heat-sealed portion with a width of 2 to 5 mm along the curved portion that bulges outward. Alternatively, mask 10 may be formed by overlapping two mask halves that have openings as ear loops at one end and a curved portion that bulges outward at the other end, and heat-sealing the mask 10 at a predetermined width of 2 to 5 mm along the curved portion. The mask 10 has a curved portion located at the center 15.

[0022] The polyol, polyisocyanate, catalyst and blowing agent contained in the composition used in the production of the flexible polyether urethane foam of the present invention will now be described. The polyol includes a polyether polyol, which includes both a diol and a polyether polyol other than a diol.

[0023] The diol may be a polyether polyol having two functional groups, which is obtained by addition polymerization of an alkylene oxide, such as ethylene oxide (EO) or propylene oxide (PO), to a dihydric alcohol, such as propylene glycol or ethylene glycol. The molecular weight of the diol is preferably 500 to 6000, more preferably 800 to 5000, and even more preferably 1500 to 4500. The hydroxyl value (OHV) of the diol is preferably 18 to 250 mgKOH / g, more preferably 22 to 140 mgKOH / g, and even more preferably 24 to 70 mgKOH / g. When the molecular weight or hydroxyl value (OHV) of the diol is within the above range, the heat sealability of the flexible polyether urethane foam becomes better. The diol is not limited to one type, and multiple types may be used in combination. The amount of diol blended is preferably 5 to 80 parts by weight, more preferably 10 to 75 parts by weight, and further preferably 30 to 75 parts by weight, and even more preferably 40 to 75 parts by weight, per 100 parts by weight of polyol, from the viewpoints of elongation and heat sealability.

[0024] Examples of polyether polyols other than diols include trivalent or higher polyhydric alcohols such as glycerin, trimethylolpropane, and pentaerythritol, and polyether polyols having three or more functional groups obtained by addition polymerization of alkylene oxides such as ethylene oxide (EO) or propylene oxide (PO) to amines such as ethylenediamine and aromatic diamines. The polyether polyol other than the diol preferably has a hydroxyl value (OHV) of 20 to 200 mgKOH / g, a functionality of 3 to 5, and a molecular weight of 1000 to 7000. The hydroxyl value (OHV) of the polyether polyol other than the diol is more preferably 24 to 150 mgKOH / g, and even more preferably 28 to 100 mgKOH / g. The molecular weight of the polyether polyol other than the diol is more preferably 1400 to 6000, and even more preferably 1800 to 5000. The polyether polyol other than the diol is not limited to one type, and multiple types may be used in combination. The polyol may contain a polymer polyol together with the polyether polyol. By containing the polymer polyol, the heat sealability of the flexible polyether urethane foam can be further improved. From the viewpoint of improving the heat sealability, the polymer polyol is preferably 5 parts by weight or more, more preferably 10 parts by weight or more, and even more preferably 20 parts by weight or more in 100 parts by weight of the polyol. The upper limit of the blending amount when the polymer polyol is blended is not particularly limited, but from the viewpoint of elongation and breathability, it is preferably 70 parts by weight or less, and even more preferably 60 parts by weight or less in 100 parts by weight of the polyol.

[0025] The polymer polyol is a polyol in which polymer particles produced by radical polymerization (graft polymerization) of monomers such as acrylonitrile and styrene in a polyether polyol are dispersed, and those usually used for the production of flexible polyurethane foams can be used. The polymer polyol preferably has a hydroxyl value (OHV) of 20 to 140 mgKOH / g, a functional group number of 3 to 5, and a molecular weight of 1000 to 7000. The hydroxyl value (OHV) of the polymer polyol is more preferably 22 to 70 mgKOH / g, and even more preferably 24 to 50 mgKOH / g. The molecular weight of the polymer polyol is more preferably 1800 to 7000, and even more preferably 2600 to 6000.

[0026] The polyisocyanate may be an aliphatic, alicyclic or aromatic polyisocyanate having two or more isocyanate groups, a mixture thereof, or a modified polyisocyanate obtained by modifying them. Examples of the aliphatic polyisocyanate include hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexamethane diisocyanate, etc., and examples of the aromatic polyisocyanate include toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate, xylylene diisocyanate, polymeric MDI (crude MDI), etc. In addition, prepolymers may also be used.

[0027] The isocyanate index (INDEX) is 90 or more, preferably 95 to 125, and more preferably 100 to 120. The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in an isocyanate by the total number of moles of active hydrogen groups such as hydroxyl groups in a polyol, and multiplying the result by 100, and is calculated as [NCO equivalent of isocyanate / active hydrogen equivalent×100].

[0028] As the catalyst, a known urethane catalyst can be used in combination. For example, amine catalysts such as triethylamine, triethylenediamine, diethanolamine, dimethylaminomorpholine, N-ethylmorpholine, and tetramethylguanidine, tin catalysts such as stannous octoate and dibutyltin dilaurate, and metal catalysts such as phenylmercury propionate and lead octenate (also called organometallic catalysts), may be used alone or in combination of the amine catalyst and the metal catalyst. The amount of the amine catalyst is preferably 0.1 to 2 parts by weight relative to 100 parts by weight of the polyol. The amount of the metal catalyst is preferably 0 to 0.5 parts by weight.

[0029] As the blowing agent, water, alternative fluorocarbons, or hydrocarbons such as pentane can be used alone or in combination. In the case of water, carbon dioxide gas is generated during the reaction of polyol with polyisocyanate, and the carbon dioxide gas causes foaming. The amount of water as the blowing agent is preferably 0.1 to 6 parts by weight, more preferably 0.8 to 5 parts by weight, and even more preferably 1.2 to 4 parts by weight, based on 100 parts by weight of polyol.

[0030] The composition may contain other auxiliaries and additives, such as foam stabilizers, colorants, antioxidants, antibacterial agents, and ultraviolet absorbing agents. The foam stabilizer may be any of those known for use in flexible polyether urethane foams, such as silicone-based foam stabilizers, fluorine-containing compound-based foam stabilizers, and known surfactants. The coloring agent is appropriately blended depending on the color required for the flexible polyether urethane foam.

[0031] The modified embodiment will be specifically described below. Transformation mode 1 The laminate 100 of variant 1 shown in FIG. 2 is composed of a laminate of a first substrate 110, a second substrate 210, and an intermediate fiber layer 310 located between the first substrate 110 and the second substrate 210.

[0032] The first substrate 110 is a flexible polyether urethane foam of the present invention, and the second substrate 210 is a flexible polyurethane foam (PUR) with an open-cell structure. Flexible polyurethane foam with an open-cell structure has excellent elongation and strength, and can obtain a high opening ratio and enhance breathability. Therefore, when used in a mask, the mask can fit to the face and can ensure good breathability. Flexible polyurethane foam with an open-cell structure includes ether-based and polyester-based types, and polyester-based types are preferred from the viewpoint of obtaining good elongation.

[0033] The open-cell flexible polyurethane foam may be a membrane-removed flexible slab polyurethane foam. The membrane-removed flexible slab polyurethane foam is obtained by removing the cell membrane from a flexible slab polyurethane foam through a known membrane-removal process. Examples of membrane-removal processes include a process for removing the cell membrane from a flexible slab polyurethane foam using a solvent, or a process for removing the cell membrane through explosion. The flexible slab polyurethane foam is formed by slab foaming, in which polyurethane foaming raw material is discharged onto a conveyer belt and foamed continuously.

[0034] The number of cells (JIS K6400-1) of the open-cell flexible polyurethane foam is preferably 40 to 110 cells / 25 mm. If the number of cells is small, the breathability increases but the strength decreases, and conversely, if the number of cells is large, the breathability decreases but the strength increases. In addition, the density (JIS K7222) of the open-cell flexible polyurethane foam is 10 to 150 kg / m 3 is preferable, and 20 to 125 kg / m 3 More preferably, 30 to 100 kg / m3 When the density is low, flexibility and light weight are increased but strength is decreased, and conversely, when the density is high, flexibility and light weight are decreased but strength is increased.

[0035] The thickness of the first substrate 110 and the second substrate 210 may be in the range of 0.5 to 2.5 mm. More preferably, the thickness of the first substrate 110 is 1.3 to 2.5 mm, and the thickness of the second substrate 210 is, for example, 0.5 to 2.5 mm, preferably 0.5 to 1.5 mm. Furthermore, the thickness of the first substrate 110 and the second substrate 210 laminated together is preferably 4.0 mm or less. If the thickness of the first substrate 110 and the second substrate 210 is too thin, the strength decreases, and conversely, if the thickness is too thick, the flexibility and breathability become poor. Furthermore, for example, it is preferable to make the thickness of the first substrate 110, on one side of which the intermediate fiber layer 310 is formed, larger than the thickness of the second substrate 210 to facilitate the formation of the intermediate fiber layer 310. In addition, when the first substrate 110 and the second substrate 210 have different thicknesses, it is preferable that the thicker side, for example, the first substrate 110, is the inhalation side (outside) and the thinner side, for example, the second substrate 210, is the suction side (face side). After sucking and removing fine particles and the like from the thicker side, for example, the first substrate 110, it is preferable to suck them from the thinner side, for example, the second substrate 210, with the nose of the face. Also, the first substrate 110 may be thinner than the second substrate 210.

[0036] The intermediate fiber layer 310 is made of nanofibers and is formed on one side of the first substrate 110 (the side facing the second substrate 210). The nanofibers can be formed by electrospinning. In this case, a polymer solution is directly sprayed from a nozzle onto one side of the first substrate 110, and a spider web-shaped intermediate fiber layer 310 of nanofibers is formed in a state of being adhered to one side of the first substrate 110. The electrospinning method uses a device consisting of a high-voltage DC power supply, an infusion pump, a stainless steel needle syringe, and a metal collector. The polymer solution is sprayed from the nozzle at the tip of the needle syringe. The nozzle and the metal collector are charged to opposite poles, and when the polymer solution is sprayed from the syringe, nanofiber fibers are deposited on the first substrate 110 placed on the collector to form a layer.

[0037] The material of the nanofiber may be any material that can form nanofibers by electrospinning, and examples thereof include thermoplastic resins such as polystyrene, polycarbonate, poly(meth)acrylate, polyvinyl chloride, polyethylene terephthalate, nylon-6,6, and nylon-4,6, polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyethylene glycol, polyethylene-vinyl acetate copolymer, polyethylene-vinyl alcohol copolymer, polyethylene oxide, biodegradable polymers such as collagen, polyacrylonitrile, polyamide, polyaniline, paraamide, polyvinyl acetate, and acetyl cellulose (acetate). In particular, polyurethane is a particularly preferred material because it has good adhesion to one side of the first substrate 110 when the nanofibers are sprayed and has good elongation. The intermediate fiber layer 310 made of polyurethane nanofibers has good followability to the elongation of the first substrate 110 and the second substrate 210, and when the laminate 100 is used as a component of a mask, the mask easily fits the face.

[0038] The diameter of the nanofibers may be within the definition of nanofibers, specifically, 1 nanometer (nm) to 1 micrometer (μm), preferably 10 nanometers (nm) to 0.8 micrometers (μm), more preferably 10 nanometers (nm) to 0.5 micrometers (μm), and even more preferably 10 nanometers (nm) to 100 nanometers (nm). If the diameter of the nanofibers is too small, viruses may pass through the nanofibers of the intermediate fiber layer 310, and conversely, if the diameter of the nanofibers is too large, the breathability of the intermediate fiber layer 310 decreases. A more preferable diameter is 10 nanometers (nm) to 100 nanometers (nm).

[0039] The weight of the intermediate fiber layer 310 made of nanofiber is not limited, but is preferably 0.10 to 0.80 g / m 2 If the basis weight is made small, the gaps between the nanofibers will become large, which may allow viruses to pass between the nanofibers, whereas if the basis weight is made large, the gaps between the nanofibers will become small, which may reduce breathability.

[0040] A manufacturing example of the laminate 100 is shown below. A long sheet of soft polyether urethane foam for the first substrate is used, and BASF thermoplastic polyurethane pellets are dissolved in a solvent on the long sheet, and a urethane nanofiber nonwoven fabric (intermediate fiber layer) is laminated and spun by electrospinning. The fiber diameter is adjusted to a predetermined diameter by the distance between the spinning nozzle and the long sheet, and the discharge amount and voltage of the nanofiber raw material discharged from the nozzle. The spun urethane nanofiber intermediate fiber layer is entangled with the long sheet of soft polyether urethane foam. The long sheet is wound on a roll, and the roll is attached to a flame welding device. A polyester-based soft urethane foam is used as the second substrate, and a roll of the second substrate is attached. The laminate 100 is obtained by laminating and conveying the roll of urethane nanofiber nonwoven fabric (intermediate fiber layer) of the roll of the first substrate while irradiating the second substrate with a flame. Instead of the soft polyether urethane foam of the first substrate, a soft polyurethane foam (soft polyester foam) may be used, or a fabric layer may be used as the substrate to form an intermediate fiber layer (nanofiber nonwoven fabric).

[0041] Transformation mode 2 As a second modified embodiment, a laminate (not shown) in which the second base material 210 of the first modified embodiment is a fabric layer will be described. The second modified embodiment is a laminate composed of a first substrate of the soft polyether urethane foam of the present invention, an intermediate fiber layer, and a second substrate of a fabric layer. The fabric layer is composed of a fabric made of fibers or yarn processed into a sheet shape. The intermediate fiber layer is formed of nanofibers similar to the intermediate fiber layer 310 of the first modified embodiment.

[0042] The fabric layer may be a knitted fabric, a woven fabric, a nonwoven fabric, or a felt fabric. The fibers constituting the fabric may be chemical fibers such as polyethylene, polypropylene, nylon, urethane, or rayon, or natural fibers such as cotton or wool. Polyester fibers are preferable from the viewpoint of durability because they are less likely to discolor due to ultraviolet rays. If the fabric has low moisture absorption, it is convenient to wash or dry the laminate of the second modified embodiment. In addition, since the fabric made of cotton or rayon has water absorption, it may be used when moisture absorption or moisture retention is required for the laminate of the second modified embodiment. The fabric may be an antibacterial fabric having antibacterial properties due to antibacterial treatment or the like. The fabric may have brushed fibers on the surface.

[0043] The fabric may be structurally elastic due to the weaving or knitting method, or may be a so-called stretch fabric that is elastic due to the use of elastic fibers having elasticity. When the fabric is a woven fabric, elastic plain weave, twill weave, or jacquard weave is preferable. When the fabric is a knitted fabric, warp knitting, flat knitting, or other fabrics may be used. For warp knitting, tricot, double raschel, etc. may be used, and for flat knitting, circular knitting, plain knitting, etc. may be used. Knitted fabrics are preferable because they have better elasticity than woven fabrics or nonwoven fabrics.

[0044] When the fabric is a nonwoven fabric, the web may be formed by any of the methods such as the dry method, the spunbond method, the meltblown method, and the airlaid method. From the viewpoint of the efficiency of collecting fine foreign matter such as bacteria, nonwoven fabrics formed by the meltblown method (meltblown nonwoven fabric) and nonwoven fabrics formed by the spunbond method (spunbond nonwoven fabric) are preferred. In addition, the fiber bonding method of the nonwoven fabric may be any of the methods such as the chemical bond method, the thermal bond method, the needle punch method, and the hydroentanglement method (spunlace), but the hydroentanglement method and the needle punch method, which have low VOCs, are preferred for the laminate for mask use.

[0045] The stretch rate of the fabric (JIS K6400-5:2004 dumbbell type 2) is preferably 50% to 500%. With a fabric having the above-mentioned stretch rate, the stretchability of the soft polyether urethane foam, which is the first base material, is not easily hindered by the fabric layer, and the stretchability of the laminate can be improved. When the laminate is used for a mask, it stretches moderately following the movement of the mouth, etc., and the burden when wearing can be reduced. In addition, when the ear hook part of the mask is formed with the laminate of the modified embodiment 2, the ear hook part is not easily broken and the burden on the ears can be reduced. In addition, it is preferable to use a fabric having a lower stretch rate than the soft polyether urethane foam, which is the first base material, because excessive stretching of the soft polyether urethane foam, which is the first base material, can be suppressed to prevent plastic deformation of the soft polyether urethane foam, and the laminate can be made strong.

[0046] The breathability of the fabric is 10cm 3 / (cm 2 sec) or more, and 3 / (cm 2 sec) or more is preferable. 3 / (cm 2 sec) or more is more preferable. 3 / (cm 2 It is particularly preferable that the air permeability of the fabric is 150 cm sec or more in relation to the foreign matter collection efficiency. 3 / (cm 2 ·sec) or less. When the breathability of the fabric is within the above range, good foreign matter collection efficiency and moderate breathability can be ensured. When the laminate of the modified embodiment 2 is used for a mask, moderate breathability can be ensured, so that breathlessness can be reduced and a good wearing feeling can be obtained. When the laminate of the modified embodiment 2 is used for a mask, good foreign matter collection efficiency can be obtained. In this way, when the breathability of the fabric is within the above range, it is preferable because it can achieve both easy breathing and good foreign matter collection efficiency. In the laminate of the modified embodiment 2, even if the breathability of the fabric layer is increased, the intermediate fiber layer can ensure foreign matter collection efficiency, so the fabric may be set by prioritizing functions such as flexibility, stretchability, and design over breathability.

[0047] The thickness of the fabric layer is preferably 0.1 mm to 0.4 mm. The thicker the fabric layer, the higher the foreign matter collection efficiency, but the greater the pressure loss of the air passing through it (the lower the breathability). The thinner the fabric layer, the lower the foreign matter collection efficiency, but the smaller the pressure loss of the air passing through it (the greater the breathability). When the fabric layer has a thickness within the above-mentioned range, the laminate of the modified embodiment 2 can obtain an appropriate breathability. Furthermore, when the fabric layer has a thickness within the above-mentioned range, the bulkiness of the laminate of the modified embodiment 2 can be suppressed.

[0048] From the viewpoint of foreign matter collection efficiency, the intermediate fiber layer is preferably made of nano-sized fibers (nanofibers). From the viewpoint of collecting finer foreign matter, the fiber diameter of the fibers is preferably 10 nm to 800 nm, more preferably 10 nm to 500 nm, and even more preferably 10 nm to 100 nm. When the fiber diameter is within the above range, collection of foreign matter and appropriate breathability can be ensured. It is preferable that the fiber diameter of the fibers constituting the intermediate fiber layer is smaller than the fibers or threads constituting the cloth layer. In this way, the cloth layer can be made relatively strong, and fine foreign matter such as bacteria that is difficult to collect by the cloth layer can be collected by the fiber layer.

[0049] Examples of the material of the fiber of the intermediate fiber layer include thermoplastic fluororesins such as polyvinylidene fluoride, polystyrene, polycarbonate, poly(meth)acrylate, polyvinyl chloride, polyethylene terephthalate, thermoplastic resins such as nylon-6,6, and nylon-4,6, polyurethane, polyvinyl alcohol, polylactic acid, polycaprolactone, polyethylene glycol, polyethylene-vinyl acetate copolymer, polyethylene-vinyl alcohol copolymer, polyethylene oxide, biodegradable polymers such as collagen, polyacrylonitrile, polyamide, polyaniline, paraamide, polyvinyl acetate, and acetyl cellulose (acetate). Polyurethane fibers are preferred because they have good adhesion to the soft polyether urethane foam of the first substrate and good elongation. If the intermediate fiber layer has good elongation, it will be able to follow the elongation of the soft polyether urethane foam and the fabric layer of the first substrate well, and for example, when the laminate of the second modified embodiment is used as a mask, it will easily fit the face.

[0050] The breathability of the middle fiber layer is 10 cm 3 / (cm 2 sec) or more, and 3 / (cm 2 sec) or more is preferable. 3 / (cm 2 sec) or more is more preferable. 3 / (cm 2 It is particularly preferable that the air permeability of the intermediate fiber layer is 150 cm sec or more in relation to the efficiency of collecting foreign matter. 3 / (cm 2 ·sec) or less. When the fiber diameter of the fibers is within the above range, the laminate of the second modified embodiment can ensure foreign matter collection efficiency and breathability. When the laminate of the second modified embodiment is used for a mask, the appropriate breathability reduces breathlessness and provides a comfortable fit. In addition, the laminate of the second modified embodiment can provide good foreign matter collection efficiency.

[0051] It is preferable to set the air permeability of the intermediate fiber layer lower than that of the soft polyether urethane foam of the first substrate. In this way, the intermediate fiber layer compensates for the foreign matter collection efficiency that cannot be obtained by the soft polyether urethane foam of the first substrate without impairing the advantages of the soft polyether urethane foam such as flexibility and elongation, and good foreign matter collection efficiency can be obtained in the laminate of the modified embodiment 2. It is also preferable to set the air permeability of the intermediate fiber layer lower than that of the cloth layer. In this way, it is preferable to set the air permeability of the intermediate fiber layer lower than that of the cloth layer. In this way, it is preferable to set the air permeability of the intermediate fiber layer lower than that of the cloth layer without impairing the advantages of the cloth layer such as flexibility and elongation, and good foreign matter collection efficiency can be obtained in the laminate of the modified embodiment 2.

[0052] The fiber weight of the intermediate fiber layer is 0.10 g / m 2 ~10g / m 2 and preferably 0.10 g / m 2 ~5g / m 2It is more preferable that the intermediate fiber layer has a fiber weight of 0.5 to 10 g / m. This ensures the efficiency of foreign matter collection and good air permeability. The fiber weight of the intermediate fiber layer can be set according to the object of foreign matter collection and the fiber diameter of the fiber layer. For example, for an intermediate fiber layer having a large fiber diameter, the fiber weight is set to 0.5 to 10 g / m. 2 , 0.5~5g / m 2 , 1~3g / m 2 For intermediate fiber layers with small fiber diameters, the fiber density is 0.1 to 1.0 g / m 2 , 0.1~0.8g / m 2 , 0.1~0.6g / m 2 In this case, it is effective in capturing small foreign matter such as bacteria and viruses.

[0053] The intermediate fibrous layer can be formed, for example, by electrospinning. For example, the first substrate is made of soft polyether urethane foam, and a polymer solution is sprayed onto one side of the substrate by electrospinning, and the fine fibers are gradually piled up to form an intermediate fiber layer. The intermediate fiber layer is laminated by bonding the fibers to the soft polyether urethane foam by entangling them. The intermediate fiber layer may be made of soft polyurethane foam (soft polyester foam) or a fabric layer as a base material instead of the soft polyether urethane foam of the first base material.

[0054] The lamination of the soft polyether urethane foam with other materials can be, for example, frame lamination or adhesion with a hot melt adhesive. Examples of the other materials include a soft polyurethane foam (soft polyester foam) and a cloth layer. As an adhesion method using a hot melt adhesive, the soft polyether urethane foam can be bonded to the other materials by sandwiching an adhesive layer such as a hot melt adhesive or applying the adhesive by a roll coater or spray coating. In this case, a nonwoven hot melt sheet can be used, or a fibrous hot melt adhesive can be applied. EXAMPLES

[0055] The compositions for producing polyurethane foam were prepared using the following components in the formulations shown in Figures 3 and 4 for the Comparative Example and each Example, and the prepared compositions for producing polyurethane foam were mixed and foamed to produce flexible polyether urethane foams. Note that no film removal treatment was performed on any of the urethane foams in the Comparative Example and each Example.

[0056] Polyether polyol other than diol; alkylene oxide-added polyether polyol, molecular weight: 3000, functionality: 3, hydroxyl value: 56 mg KOH / g, product name: GP3050N, manufactured by Sanyo Chemical Industries, Ltd. Polymer polyol; molecular weight: 5000, functionality: 3, hydroxyl value: 32 mgKOH / g, product name: Exenol 941 (60% by mass of polyether polyol obtained by addition polymerization of propylene oxide to glycerin, graft-polymerized with 40% by mass of a mixture of styrene:acrylonitrile with a mass ratio of 8:2, and dispersed; solid content: 40%) Diol 1: Polyether polyol, molecular weight: 1000, functionality: 2, hydroxyl value: 108-116 mgKOH / g, product name: Actocol D1000, manufactured by Mitsui Chemicals, Inc. Diol 2: Polyether polyol, molecular weight: 2000, functionality: 2, hydroxyl value: 54-58 mgKOH / g, product name: Actocol D2000, manufactured by Mitsui Chemicals, Inc. Diol 3: Polyether polyol, molecular weight: 4000, functionality: 2, hydroxyl value: 26-30 mgKOH / g, product name: Actocol D4000, manufactured by Mitsui Chemicals, Inc. Foam stabilizer: Silicone foam stabilizer, product name: SZ1136, manufactured by Dow Toray Amine catalyst: N-ethylmorpholine, product name: Kao Raiser No. 22, manufactured by Kao Corporation Tin catalyst; Stannous octoate, product name: MRH110, manufactured by Johoku Chemical Industry Co., Ltd. Foaming agent: water Isocyanate; Product name: Cosmonate T-80 / T-65, manufactured by Tosoh Corporation

[0057] The physical properties of the polyurethane foam produced were measured, including density (in accordance with JIS K7222), tensile strength (in accordance with JIS K 6400-5K), elongation (in accordance with JIS K6400-5), heat seal strength (adhesive strength), and breathability (in accordance with JIS L1096A method), as well as odor.

[0058] The heat seal strength was measured by overlapping two test pieces measuring 100 mm in length, 30 mm in width, and 10 mm in thickness, and heat sealing them by sandwiching a 20 mm area from one end (the 30 x 20 mm part) between hot plates at 180°C and applying a pressure of 1.3 MPa (megapascals) for 30 seconds. After that, using an autograph (manufactured by Shimadzu Corporation), a 20 mm area from the other end of the two test pieces was held with a gripper, opened 180 degrees, and pulled in opposite directions at a tensile speed of 500 mm / min. The strength at which the two test pieces peeled off was measured, and this was taken as the heat seal strength. The odor was checked by a sensory test in which subjects were asked to smell the product and evaluate whether or not it had an odor.

[0059] The heat seal strength measurement results were judged according to the following criteria. The heat seal strength was judged as "x" if it was less than 100 kPa, "o" if it was 100 to less than 500 kPa, and "◎" if it was 500 kPa or more. The measurement results and evaluation results are shown in FIG.

[0060] The results of the comparative examples and each example are shown below. Comparison example The comparative example is an example in which a polyether polyol other than a diol was used alone as the polyol. The comparative example has a density of 52.5 kg / m 3 , tensile strength 64.1kPa, elongation 98.6%, heat seal strength is no seal (no adhesion), breathability 12.0cm 3 / cm 2 / sec, no odor was detected, and the heat seal strength was judged to be "x".

[0061] Examples 1 to 5 are examples in which the polyol is composed of a polyether polyol other than the diol, and diol 2 (molecular weight 2000), and the blending ratio of diol 2 (molecular weight 2000) in the polyol is changed.

[0062] Example 1 Example 1 is an example in which the amount of Diol 2 (molecular weight 2000) was 10.0 parts by weight. Example 1 has a density of 53.0 kg / m 3 , tensile strength 73.0kPa, elongation 135.0%, heat seal strength 389.0kPa, breathability 21.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was judged to be "good."

[0063] Example 2 Example 2 is an example in which the amount of Diol 2 (molecular weight 2000) was 20.0 parts by weight. Example 2 has a density of 53.4 kg / m 3 , tensile strength 78.8kPa, elongation 164.9%, heat seal strength 473.0kPa, breathability 39.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was judged to be "good."

[0064] Example 3 Example 3 is an example in which the amount of diol 2 (molecular weight 2000) was 30.0 parts by weight. Example 3 has a density of 52.6 kg / m 3 , tensile strength 77.5kPa, elongation 209.5%, heat seal strength 573.8kPa, breathability 94.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0065] Example 4 Example 4 is an example in which the amount of diol 2 (molecular weight 2000) was 50.0 parts by weight. Example 4 has a density of 52.4 kg / m 3, tensile strength 100.1kPa, elongation 305.5%, heat seal strength 791.6kPa, breathability 122.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0066] Example 5 Example 5 is an example in which the amount of diol 2 (molecular weight 2000) was 70.0 parts by weight. Example 5 has a density of 52.3 kg / m 3 , tensile strength 105.5kPa, elongation 511.0%, heat seal strength 854.1kPa, breathability 147.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0067] Example 6 Example 6 is an example in which the amount of polyether polyol other than the diol in Example 4 was reduced from 50.0 parts by weight to 20.0 parts by weight, and 30.0 parts by weight of polymer polyol was blended instead. Example 6 has a density of 29.8 kg / m 3 , tensile strength 124.0kPa, elongation 261.0%, heat seal strength 1517.1kPa, breathability 120.0cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0068] Examples 7 to 9 are examples in which the polyol is composed of a polyether polyol other than the diol and diol 3 (molecular weight 4000), and the blending ratio of diol 3 (molecular weight 4000) in the polyol is changed.

[0069] Example 7 Example 7 is an example in which the amount of Diol 3 (molecular weight 4000) was 10.0 parts by weight. Example 7 has a density of 51.7 kg / m 3 , tensile strength 76.3kPa, elongation 152.9%, heat seal strength 550.7kPa, breathability 33.9cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0070] Example 8 Example 8 is an example in which the amount of Diol 3 (molecular weight 4000) was 30.0 parts by weight. Example 8 has a density of 52.4 kg / m 3 , tensile strength 74.1kPa, elongation 175.0%, heat seal strength 667.8kPa, breathability 78.5cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0071] Example 9 Example 9 is an example in which the amount of Diol 3 (molecular weight 4000) was 70.0 parts by weight. Example 9 has a density of 62.1 kg / m 3 , tensile strength 66.8kPa, elongation 244.7%, heat seal strength 627.5kPa, breathability 46.1cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0072] Examples 10 and 11 are examples in which the polyol is composed of a polyether polyol other than the diol, and diol 1 (molecular weight 1000), and the blending ratio of diol 1 (molecular weight 1000) in the polyol is changed.

[0073] Example 10 Example 10 is an example in which the amount of Diol 1 (molecular weight 1000) blended was 10.0 parts by weight. Example 10 has a density of 49.8 kg / m 3 , tensile strength 71.6kPa, elongation 152.2%, heat seal strength 540.1kPa, breathability 13.8cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎". Example 11 Example 11 is an example in which the amount of Diol 1 (molecular weight 1000) blended was 30.0 parts by weight. Example 11 has a density of 49.6 kg / m3 , tensile strength 84.7kPa, elongation 215.5%, heat seal strength 740.1kPa, breathability 9.2cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0074] Examples 12 to 15 are examples in which a polymer polyol was blended with a polyol, and the blending ratio was changed.

[0075] Example 12 Example 12 is an example in which the blend amount of polyether polyol other than diol was 30.0 parts by weight, the blend amount of polymer polyol was 10.0 parts by weight, and the blend amount of diol 2 (molecular weight 2000) was 60.0 parts by weight. Example 12 has a density of 55.2 kg / m 3 , tensile strength 115.5kPa, elongation 241.4%, heat seal strength 798.0kPa, breathability 24.7cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0076] Example 13 Example 13 is an example in which the blend amount of polyether polyol other than diol was 20.0 parts by weight, the blend amount of polymer polyol was 30.0 parts by weight, and the blend amount of diol 2 (molecular weight 2000) was 50.0 parts by weight. Example 13 has a density of 54.8 kg / m 3 , tensile strength 150.7kPa, elongation 236.6%, heat seal strength 1066.2kPa, breathability 41.9cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0077] Example 14 Example 14 is an example in which the blending amount of polyether polyol other than diol was 0 part by weight, the blending amount of polymer polyol was 50.0 parts by weight, and the blending amount of diol 2 (molecular weight 2000) was 50.0 parts by weight. Example 14 has a density of 53.9 kg / m 3, tensile strength 168.0kPa, elongation 205.6%, heat seal strength 1055.9kPa, breathability 53.6cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0078] Example 15 Example 15 is an example in which the blending amount of polyether polyol other than diol was 0 part by weight, the blending amount of polymer polyol was 70.0 parts by weight, and the blending amount of diol 2 (molecular weight 2000) was 30.0 parts by weight. Example 15 has a density of 55.2 kg / m 3 , tensile strength 166.4kPa, elongation 103.5%, heat seal strength 1156.8kPa, breathability 6.4cm 3 / cm 2 / sec, no odor, and the heat seal strength was rated as "◎".

[0079] As described above, the heat seal strength of the flexible polyether urethane foam was increased by blending the polymer polyol in Examples 6 and 12 to 15. Furthermore, the heat seal strength can be further increased by increasing the blending ratio of the polymer polyol in the polyol.

[0080] As described above, the flexible polyether urethane foam of the present invention has heat sealability and is therefore suitable for applications requiring bonding (adhesion) by heat sealing. The flexible polyether urethane foam of the present invention has an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 Therefore, it is suitable as a material for urethane masks, which require stretchability. Furthermore, the soft polyether urethane foam of the present invention is less susceptible to hydrolysis than polyester urethane foam, and therefore is less susceptible to deterioration due to washing and the like, and has high durability, so that it can be used in urethane masks and washed repeatedly. The present invention is not limited to the embodiments, and can be modified without departing from the spirit of the invention. [Industrial Applicability]

[0081] The flexible polyether urethane foam of the present invention is suitable for urethane masks. [Explanation of symbols]

[0082] 10. Mask 13 Ear opening 15 Central part 16 Heat seal part

Claims

1. The raw material contains a polyether polyol having two functional groups obtained by addition polymerization of a polymer polyol and an alkylene oxide, Elongation (based on JIS K6400-5) is 100% or more, density (based on JIS K7222) is 10 to 150 kg / m 3 And, A flexible polyether urethane foam characterized in that the result of the heat seal strength test shown below is 100 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

2. The molecular weight of the polymer polyol is 1,800 to 7,000. The flexible polyether urethane foam according to claim 1.

3. A flexible polyether urethane foam formed from a composition for producing polyurethane foam, the composition comprising a polyol, a polyisocyanate, a catalyst, and a blowing agent, The polyol includes a polyether polyol, The polyether polyol includes a diol and a polyether polyol other than the diol, The diol includes a polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide, the diol has a hydroxyl value of 70 mgKOH / g or less, and contains 40 parts by weight or more of the diol per 100 parts by weight of the polyol; The soft polyether urethane foam has an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 And, A flexible polyether urethane foam characterized in that the result of the heat seal strength test shown below is 100 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

4. A flexible polyether urethane foam formed from a composition for producing polyurethane foam, the composition comprising a polyol, a polyisocyanate, a catalyst, and a blowing agent, The polyol includes a polyether polyol, The polyether polyol includes a diol and a polyether polyol other than the diol, The diol includes a polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide, the molecular weight of the diol is 4000 or more, and the diol is contained in an amount of 70 parts by weight or more per 100 parts by weight of the polyol; The soft polyether urethane foam has an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 And, A flexible polyether urethane foam characterized in that the result of the heat seal strength test shown below is 100 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

5. A polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide as a raw material, Elongation (based on JIS K6400-5) is 205.6% or more, density (based on JIS K7222) is 10 to 150 kg / m 3 And, A flexible polyether urethane foam characterized in that the result of the heat seal strength test shown below is 100 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

6. A polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide as a raw material, Elongation (based on JIS K6400-5) is 100% or more, density (based on JIS K7222) is 10 to 150 kg / m 3 And, A flexible polyether urethane foam, characterized in that the result of the heat seal strength test shown below is 389.0 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

7. A flexible polyether urethane foam formed from a composition for producing polyurethane foam, the composition comprising a polyol, a polyisocyanate, a catalyst, and a blowing agent, The polyol includes a polyether polyol, The polyether polyol includes a diol and a polyether polyol other than the diol, The diol includes a polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide, The soft polyether urethane foam has an elongation (based on JIS K6400-5) of 100% or more and a density (based on JIS K7222) of 10 to 150 kg / m 3 And, A soft polyether urethane foam (excluding those containing phosphorus) characterized in that the result of the heat seal strength test shown below is 100 kPa or more. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

8. A urethane mask comprising the soft polyether urethane foam according to any one of claims 1 to 7.

9. Elongation (based on JIS K6400-5) is 100% or more, density (based on JIS K7222) is 10 to 150 kg / m 3 , breathability (JIS L1096A compliant) is 5 cm 3 / cm 2 / sec or more, The present invention is provided with a soft polyether urethane foam having a result of 100 kPa or more in a heat seal strength test shown below, The urethane mask is characterized in that the soft polyether urethane foam contains, as a raw material, a polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

10. Elongation (based on JIS K6400-5) is 100% or more, density (based on JIS K7222) is 10 to 150 kg / m 3 And, The laminate has at least a fabric layer laminated on a soft polyether urethane foam having a heat seal strength test result of 100 kPa or more as described below, The urethane mask is characterized in that the soft polyether urethane foam contains, as a raw material, a polyether polyol having two functional groups obtained by addition polymerization of an alkylene oxide. The heat seal strength test was carried out by stacking two test pieces each measuring 100 mm long x 30 mm wide x 10 mm thick. The area of ​​20 mm from one end was heat sealed by clamping it between hot plates at 180° C. and applying a pressure of 1.3 MPa for 30 seconds. The other ends of the two test pieces are opened by 180 degrees and pulled in opposite directions at a pulling speed of 500 mm / min. The strength at which the two test pieces peel apart is defined as the heat seal strength.

Citation Information

Patent Citations

  • Production of flexible polyurethane foam

    JP1992031419A

  • Composition for polyurethane foam

    JP1995149854A

  • Urethane foam and its production

    JP1997151234A

  • Flexible polyurethane slab foam and its production

    JP2001002749A

  • String for mask

    JP2002065878A